A Novel Tool for Making Policy Recommendations Based on PVA: Helping Theory Become Practice. Issue 3 (17th November 2014) - Robinson, Orin J.; Lockwood, Julie L.; Stringham, Oliver C.; Fefferman, Nina H.
Abstract Mathematical models have long been used to aid in conservation decision‐making, however there are many objections to their use by conservation practitioners. Two common objections are that model outputs are too uncertain and are often not communicated effectively. Population viability analysis (PVA) often makes use of mathematical models and has become a mainstay in conservation management; however, it is not immune to these problems. Here we provide a simple method for using the output of PVA models to calculate the probability of management achieving "success" and "failure, " as well as the probability that implementing management will be no more effective than doing nothing at all. Using our method with 14 previously published PVAs, we show that expected probability of success varied from 0.14 to 0.98, failure from 0.054 to 0.6, and the probability management was not needed varied from 0.015 to 0.47. Calculating and reporting these probabilities provide conservation practitioners and policy‐makers with more intuitive and tangible ways of identifying potential risks and rewards to their actions.